2021
DOI: 10.1101/2021.07.26.453814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trehalose increases tomato drought tolerance, induces defenses, and increases resistance to bacterial wilt disease

Abstract: Ralstonia solanacearum causes plant bacterial wilt disease, leading to severe crop losses. Xylem sap from R. solanacearum-infected tomato is enriched in host produced trehalose. Water stressed plants accumulate the disaccharide trehalose, which increases drought tolerance via abscisic acid (ABA) signaling networks. Because infected plants have reduced water flow, we hypothesized that bacterial wilt physiologically mimics drought stress, which trehalose could mitigate. Transcriptomic responses of susceptible vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 179 publications
(288 reference statements)
0
6
0
Order By: Relevance
“…Trehalose is also involved in plant–pathogen interactions, but the exact mechanism remains unclear. It is required for the infectivity of pathogens [ 64 ], and at the same time, exogenous trehalose elicits plant defense responses and endogenous trehalose signals microbial pathogen attack [ 65 , 66 ]. In our study, Psl induced trehalose accumulation, which was virtually absent from control leaves at 0 and 2 day.…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose is also involved in plant–pathogen interactions, but the exact mechanism remains unclear. It is required for the infectivity of pathogens [ 64 ], and at the same time, exogenous trehalose elicits plant defense responses and endogenous trehalose signals microbial pathogen attack [ 65 , 66 ]. In our study, Psl induced trehalose accumulation, which was virtually absent from control leaves at 0 and 2 day.…”
Section: Discussionmentioning
confidence: 99%
“…Several aromatics have been detected and quantified in tomato xylem sap during infection with phyl. I strain GMI1000: salicylic acid (∼20-200 nM), benzoic acid (∼10 nM), and coumaric acid (∼100 nM) (34). Our analyses found that phyl.…”
Section: Discussionmentioning
confidence: 99%
“…The co-application of MT and SA markedly improved plant functions such as the photosynthetic pigments content, photochemical reactions of photosynthesis, net photosynthetic rate, transpiration rate, stomatal conductance, as well as the osmoprotectants accumulation [ 62 ]. In the case of trehalose, it is well known that this disaccharide, which is produced by various species of PGPB, plays important roles in plant and microbial resistance to heat, drought, salt, cold stress, or even resistance to biotic factors, such as bacterial pathogens [ 63 , 64 , 65 ]. In this case, the application of trehalose and SA decreased the negative effects of drought stress on sweet basil plants.…”
Section: Salicylic Acidmentioning
confidence: 99%